2020
DOI: 10.1371/journal.pone.0239796
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmological emergencies and the SARS-CoV-2 outbreak

Abstract: Since the end of 2019, an outbreak of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), originating in the Chinese city of Wuhan has spread rapidly worldwide causing thousands of deaths. Coronavirus disease (COVID-19) is supported by SARS-CoV-2 and represents the causative agent of a potentially fatal disease that is of great global public health concern. Italy has been the first European country recording an elevated number of infected forcing the Italian Government to call for total lockdown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
33
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 13 publications
10
33
2
Order By: Relevance
“…to 14.1 percentage points. 8,9 These findings were in line with those found by the current study, as would be expected from studies carried out in similar public healthcare institutions in the midst of the pandemic.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…to 14.1 percentage points. 8,9 These findings were in line with those found by the current study, as would be expected from studies carried out in similar public healthcare institutions in the midst of the pandemic.…”
Section: Discussionsupporting
confidence: 93%
“…These studies found a 65% to 73% decrease in the number of ophthalmic emergencies in 2020 in comparison to a comparable period. [8][9][10] Comparatively emergent diagnoses were agreed to have increased by 7.4 to 11…”
Section: Discussionmentioning
confidence: 99%
“…Fear of going to a hospital and exposure to a possible risk of infection appeared to be a critical factor in this decline as other publications suggests. 12 In accordance with our hypothesis, emergent visits increased by 5.91% and non-emergent visits decreased by 6.58%, however, the decline of the non-emergent visits were not as signi cant as expected. A decrease of less than 10 per cent, although signi cant (p<0.001), indicates that patients with non-emergent conditions do not understand the severity of their pathology, and continue to present at ED.…”
Section: Discussionsupporting
confidence: 88%
“…This reduction in the number of OE coincides with a publication that studied the number of visits to the ED globally during a similar period in Norway where the reduction of visits varied from 21% to 39% depending on the studied week, 10 and with other publications that described the effects of the pandemic on OE in speci c hospitals where the reduction of visits decreased more than 50%. [11][12][13] . Fear of going to a hospital and exposure to a possible risk of infection appeared to be a critical factor in this decline as other publications suggests.…”
Section: Discussionmentioning
confidence: 99%
“…We included patients with an acute need for treatment as an inpatient, regardless of whether surgery was indicated or not. This has to be considered when comparing the numbers from this setting to other studies reporting on emergency department visits (8,9) or ophthalmic surgical care (10).…”
Section: Discussionmentioning
confidence: 99%